Molecular and Cellular Dynamics in the Skin, the Lymph Nodes, and the Blood of the Immune Response to Intradermal Injection of Modified Vaccinia Ankara Vaccine - Rosenbaum, Pierre; Tchitchek, Nicolas; Joly, Candie; Stimmer, Lev; Hocini, Hakim; Dereuddre-Bosquet, Nathalie; Beignon, Anne-Sophie; Chapon, Catherine; Levy, Yves; Le Grand, Roger; Martinon, Frédéric (Frontiers in Immunology, 2018)
New vaccine design approaches would be greatly facilitated by a better understanding of the early systemic changes, and those that occur at the site of injection, responsible for the installation of a durable and oriented protective response. We performed a detailed characterization of very early infection and host response events following the intradermal administration of the modified vaccinia virus Ankara as a live attenuated vaccine model in non-human primates. Integrated analysis of the data obtained from in vivo imaging, histology, flow cytometry, multiplex cytokine, and transcriptomic analysis using tools derived from systems biology, such as co-expression networks, showed a strong early local and systemic inflammatory response that peaked at 24 h, which was then progressively replaced by an adaptive response during the installation of the host response to the vaccine. Granulocytes, macrophages, and monocytoid cells were massively recruited during the local innate response in association with local productions of GM-CSF, IL-1β, MIP1α, MIP1β, and TNFα. We also observed a rapid and transient granulocyte recruitment and the release of IL-6 and IL-1RA, followed by a persistent phase involving inflammatory monocytes. This systemic inflammation was confirmed by molecular signatures, such as up-regulations of IL-6 and TNF pathways and acute phase response signaling. Such comprehensive approaches improve our understanding of the spatiotemporal orchestration of vaccine-elicited immune response, in a live attenuated vaccine model, and thus contribute to rational vaccine development.